Supply-side structural reform from the perspective of political economy - Min Fang (China Political Economy (CPE), 2019)
Purpose Deepening supply-side structural reform is the main objective of the economic work since the Chinese economy entered a new stage of development. By adopting the fundamental principles and methodologies of Marxist political economy, the authors can provide clarifications on the three basic theoretical issues concerning the supply-side structural reform. The paper aims to discuss these issues. Design/methodology/approach First, the essential starting point for understanding the supply-side structural reform is the primacy of production, as well as the organic connection between production and consumption in social reproduction, rather than the supply and demand as superficially seen in exchanges. By identifying the right starting point, the authors can avoid alternating between demand and supply management, and between liberalism and interventionism. Findings Structural problems, which are closely related to the institutional structure of production and the purpose and nature of production, cannot be solely attributed to the imbalance caused by market failures. Chinese economy has suffered prolonged structural contradictions and structural problems. Originality/value To decide whether the financial and the real estate sectors are real economy or virtual economy, the key is to examine whether the monetary capital used in financial activities and real estate commodity (capital) go through the capital circulation process of from monetary capital to productive capital and further to commodity capital, and whether the capital gain is generated by the value appreciation of capital or the value transfer and distribution as a result of the transfer of ownership. With its emphasis on developing the real economy, the supply-side structural reform should foster both development of manufacturing, and parts of financial and real estate sectors that are the real economy.
Keywords: 330; Political economy of supply-side structural reform; Structural contradictions; Virtual economy